Gay and lesbian communities the world over - Simon, Rita J. (Rita James), 1931-2013 (The world over ;, 2009)
Gay and Lesbian Communities the World Over provides an innovative examination and comparison of the treatment and status of gays and lesbians in 21 countries. The book contains a country-by-country profile of each of the issues, describes treatment and status, reports on the pubic opinion data, and compares countries against each other.